Cultivating a Tolerant Generation, Integrating Islamic Values with Local Wisdom in Education - Mala, Asnal; Badriyah, Laila; Mufaizah, Mufaizah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This study aims to explore the integration of Islamic values and local wisdom in education as an effort to cultivate a tolerant generation. Utilizing a case study method, the research was conducted in several schools that implement a curriculum based on these values. Data were collected through interviews, observations, and document analysis to understand the implementation of these values in the teaching and learning process. The findings indicate that the integration of Islamic values and local wisdom significantly contributes to the enhancement of students' attitudes toward tolerance. Education that combines Islamic values with local wisdom not only enriches the learning experience but also fosters the character of a tolerant and inclusive generation. This research contributes to the development of a more holistic curriculum to be applied in educational institutions.